Learning Ownership PBL Approach Enhancing Concept Understanding on Student - Prabaningtyas, Sitoresmi; Risqillah, Ulfi (BIOEDUKASI, 2024)
Through a process known as "Learning Ownership," students actively engage in the educational process and gain an understanding of the context, goal, and application of the material they have studied. The abilities and routines needed to acquire ownership are quite adaptable and can be used in any type of learning setting. Aim of this study was to unveil the effect of learning ownership-PBL model on students' concept understanding. The sampling technique used on this research was the random sampling technique that consisted of 2 group: the control group use PBL model and the experimental group uses learning ownership-PBL model. For learning ownership parameter we use a questionnaire consisting of 33 questions and for critical thinking parameter use multiple choice consisting of 10 questions. The test used is an independent sample T-test and Spearman test to see correlation between learning ownership and critical thinking skill. The analysist revealed that student in experimental group have learning ownership and concept understanding score improvement higher than PBL model alone in all indicators. The learning ownership-PBL is moderately correlated and significantly increase students concept understandings. Thus, we conclude that learning ownership-PBL can increase student concept understandings.